Sustainable tourism practices through the eyes of the tourist: a case study of a tour operator - Calnaryte, Laura (2016)
This internship report aim was to find out the importance of sustainable tourism practices from a tourist point of view. The research study and internship took place at Back-Roads Touring - a tour operator (based in London) that specializes in small group touring for seniors travellers from Australia, New Zealand, USA and Canada. Google Forms online questionnaire was used in order to answer the objectives of the study. In total 1322 clients received an online questionnaire out of which 182 filled in the survey. The study had four objectives, however the main focus was to find out which tourism practices ( out of 15 choices) were the most important to the respondents during a Back-Roads Tour and which tourism options (using the same 15 choices) the respondents identify as sustainable tourism options ( objective 2 and 3). The results showed that the respondents valued the most small group touring and having an experienced tour leader, which are the core practices of the company. Furthermore, the respondents were not seeking for more sustainable tourism practices neither willing to donate money to local charities/non- profit organizations. This finding shows that the clients are content with a current model of a tour, are willing to return, however price and quality will be play a key role in the decision. The respondents´ lack of wish to support or donate money to charities /non-profit organizations, could be due to the fact that most of the clients were from middle class thus they did not have enough disposable income. Moreover, one of the objectives of this study was to find out if the clients valued sustainable tourism certification. The results showed that the respondents’ were not aware of the sustainable tourism certification that the company obtained, however slightly over half of the respondents said that the knowledge of the certification has positively influenced them to travel again with a company.